CIVIC EDUCATION LEARNING BASED ON ENVIRONMENTAL ISSUES TO STRENGTHEN CIVIC RESPONSIBILITY OF PGSD STUDENTS - Prasetiyo, Dwi Agung (PREMIERE : Journal of Islamic Elementary Education, 2025)
Abstract The purpose of this study is to review and synthesize existing literature on the application of environmentally-based Civic Education learning to enhance the civic responsibility of Elementary School Teacher Education students. As future educators, Elementary School Teacher Education students play a crucial role in developing the ideals of civic responsibility and environmental sustainability. This study uses a literature review technique, examining various important scientific sources on the integration of Civic Education, Environmental Education, and the idea of ​​Ecological Citizenship. The research findings indicate that contextualizing Civic Education with environmental issues can enhance students' civic knowledge, abilities, and dispositions by increasing ecological awareness, critical attitudes towards environmental challenges, and active involvement in sustainability initiatives. Furthermore, it is revealed that the integration of environmental issues into Civic Education has not been regularly implemented at the tertiary level, particularly in Elementary School Teacher Education study programs. This study provides a conceptual model of civic learning that focuses on environmental concerns, emphasizing the development of ecological civic responsibility obligations.